2021
DOI: 10.3389/fphar.2021.651497
|View full text |Cite
|
Sign up to set email alerts
|

Boldenone Undecylenate-Mediated Hepatorenal Impairment by Oxidative Damage and Dysregulation of Heat Shock Protein 90 and Androgen Receptors Expressions: Vitamin C Preventive Role

Abstract: Boldenone Undecylenate (BLD) is a synthetic derivative of testosterone and a widely used anabolic androgenic steroid. The health risk of BLD use as a pharmaceutical or dietary supplement is still underestimated and under-reported. Vitamin C (VC) has been recognized as an antioxidant with prominent hepatorenal protective effects. This study investigated the possible preventive activity of VC against BLD-induced hepatorenal damage. Forty adult male Wistar rats were classified into five groups: control, vehicle c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 121 publications
0
4
0
Order By: Relevance
“…Moreover, on the basis of their results after treatment with androgens at a high dosage, FSH, LH, and testosterone hormone levels statistically decreased, whereas prolactin and estrogen hormones increased. Behairy et al [12 ▪ ,13 ▪ ], in two different studies, demonstrated several parameters (such as serum testosterone, acid phosphatase, sorbitol dehydrogenase, sperm abnormalities and testicular malondialdehyde) were significantly increased in the androgen-treated group. The same group demonstrated that the vitamin C co-administration may attenuate the adverse effects of androgens.…”
Section: Resultsmentioning
confidence: 98%
“…Moreover, on the basis of their results after treatment with androgens at a high dosage, FSH, LH, and testosterone hormone levels statistically decreased, whereas prolactin and estrogen hormones increased. Behairy et al [12 ▪ ,13 ▪ ], in two different studies, demonstrated several parameters (such as serum testosterone, acid phosphatase, sorbitol dehydrogenase, sperm abnormalities and testicular malondialdehyde) were significantly increased in the androgen-treated group. The same group demonstrated that the vitamin C co-administration may attenuate the adverse effects of androgens.…”
Section: Resultsmentioning
confidence: 98%
“…Boldenone, a 1(2)-dehydrogenated analogue of testosterone, differs chemically from testosterone by a double bond between C1 and C2. It is characterized by high anabolic and low androgenic activity and due to its effects muscles grow slower but is of better quality than most testosterone derivatives [ 54 , 55 , 56 ]. It is approved as a veterinary drug in many countries, especially for the treatment of horses, calves, and lambs [ 57 , 58 ].…”
Section: The Most Commonly Used or Misused Anabolic Steroidsmentioning
confidence: 99%
“…Despite being banned in humans, boldenone is still available illegally and heavily used by athletes and body builders and for fitness purposes in non-athletics [ 5 ]. Several health disorders have been associated with boldenone misuse like renal damage [ 6 ], cardiovascular disorders [ 7 ], liver dysfunction [ 8 ], and testicular problems [ 9 ] These actions were attributed to the adverse effects of boldenone on the antioxidant mechanisms of these organs [ 7 ]. In addition, a wide range of behavioral and neurochemical alterations have been reported in the nervous system after AAS consumption [ 10 ].…”
Section: Introductionmentioning
confidence: 99%